Development of Highly Efficient SOFC Using Two-Stage Stacks System and Fuel Regeneration in Tokyo Gas. (10th July 2019) - Dohkoh, Tatsuki; Akabane, Shunnosuke; Shirai, Marie; Nakajima, Tatsuya; Kawabata, Yasuharu; Ide, Takahiro; Nakamura, Kazuo; Hatae, Toru
Abstract : Tokyo Gas has developed a highly efficient solid oxide fuel cell system by increasing the fuel utilization rate using two-stage stacks and fuel regeneration. We focused on the separation membrane, which removes both steam and carbon dioxide from the anode off-gas of the first-stage stack. In this study, we evaluated the gas separation properties of the membrane module. We connected the membrane module to our fifth-generation hot module and evaluated the power generation performance. The results show DC efficiency of 74.8%LHV at a gross power output of 4.89 kW. In addition, we applied both the separate membrane module and steam condenser to our fifth-generation hot module. This system demonstrated 67.4%LHV DC efficiency at a gross power output of 4.93 kW.